DEVELOPING A CONCEPTUAL FRAMEWORK FOR MEDIUM-SIZED ENTERPRISE INTERNATIONALIZATION: AN INCREMENTAL AND CIRCULAR PROCESS-ORIENTED APPROACH TO EFFECTIVE EXPORT MANAGEMENT - Gatto, Luca; Nasta, Luigi; Pirolo, Luca (Piccola Impresa / Small Business, 2025)
Purpose. This study aims to provide a comprehensive and structured guide for Medium-sized Enterprises preparing to develop international markets. It introduces an incremental and circular four-step export management process that includes export readiness assessment, market selection, export business plan development, and implementation. Design/methodology/approach. The study integrates various strategic tools and theoretical perspectives, including Porter's Five Forces, PESTEL analysis, SWOT analysis, and the CANVAS model, to create a process-oriented framework tailored for medium-sized enterprises internationalization. The research draws from existing literature and practical insights to construct a detailed and actionable guide for practitioners. Findings. The proposed incremental and circular four-step export management process delineates a structured pathway for medium-sized enterprises to navigate internationalization effectively. It emphasizes the importance of ongoing monitoring, value chain adaptation, and collaboration, providing a process-based framework that challenges traditional theories of gradual market knowledge accumulation and network reliance. The study highlights the Export Business Plan as a central element in the internationalization process. Practical and Social implications. The framework offers practical implications for medium-sized enterprises training and development, providing a foundational structure for preparing employees and practitioners for international roles. It advocates for a balanced, data-driven approach that integrates subjective relationship-building with objective market research and strategic planning, enhancing resource utilization and increasing the likelihood of successful market entry. Additionally, the study suggests that internationalization should be viewed as a strategic, structured initiative, enabling Medium-sized Enterprises to anticipate challenges, manage risks, and remain agile in fluctuating market conditions. Originality of the study. This study contributes a novel perspective by positioning the Export Business Plan as a central element of the internationalization process, enriching existing theoretical frameworks, and encouraging further research into the strategic planning aspects of medium-sized enterprises internationalization. It offers a fresh viewpoint that may prompt a reevaluation of traditional stage models, emphasizing flexibility and adaptability in medium-sized enterprises internationalization strategies.